Mechanistic evidence and efficiency of the Cr(VI) reduction in water by different sources of zerovalent irons - Yang, J.E.; Kim, J.S.; Ok, Y.S.; Yoo, K.R. (Water science and technology, 2007)
The objective of this research was to assess the mechanism and effectiveness of the zerovalent iron (ZVI) to remediate the Cr(VI) contaminated water. The mechanism of Cr(VI) reduction by ZVI was evaluated by characterising surface properties and chemical compositions of Fe and Cr products using SEM-EDS, XRD and XPS analyses. The effectiveness of ZVI in Cr(VI) reduction was assessed by the luminescent bacteria (Photobacterium Phosphoreum). The Cr(VI) was reduced to Cr(III), when the reactive Fe0 was oxidised to Fe(II,III), showing the presence of Fe2O3, (Fe-Cr)2O3 and FeOOH. The SEM-EDS analysis showed that ZVI with a higher reducing capacity was more subject to changes of surface and morphological properties due to ionisation of ZVI. The Cr and Fe in precipitates subsisted exclusively in the Cr(III) or Fe(III) states with the respective forms of Cr(OH)3 or Cr2O3 and FeOOH or Fe2O3. Electrons produced from ZVI oxidation reduced Cr(VI) to Cr(III), thus resultantly Cr(III) precipitated or co-precipitated with Fe(III) to form Fe(III)-Cr(III) hydroxide or Fe(III)-Cr(III) oxyhydroxide. Toxicity of water reacted with ZVI was significantly lower than that of the untreated water.